Induction chemotherapy with paclitaxel, carboplatin, and cetuximab (PCE) followed by chemoradiotherapy for unresectable locoregional recurrence after curative surgery in patients with squamous cell carcinoma of the head and neck - Sato, Masanobu; Enokida, Tomohiro; Fujisawa, Takao; Okano, Susumu; Takeshita, Naohiro; Tanaka, Nobukazu; Tanaka, Hideki; Motegi, Atsushi; Zenda, Sadamoto; Shinozaki, Takeshi; Matsuura, Kazuto; Hayashi, Ryuichi; et al. (Frontiers in Oncology, 2024)
The significance of induction chemotherapy (IC) in the treatment of squamous cell carcinoma of the head and neck (SCCHN) with unresectable locoregional recurrence after curative surgery has not been clarified.The aim of this study was to evaluate the efficacy of IC followed by chemoradiotherapy (CRT) in these patients.Methods: Among patients with unresectable locoregional recurrent SCCHN who had not undergone prior irradiation and were eligible for cisplatin, we conducted a retrospective analysis of patients who received CRT following IC with paclitaxel, carboplatin, or cetuximab (IC-PCE group) and those who received CRT without prior IC (CRT group) between June 2013 and August 2021.Result: Forty-two patients were included. The CRT group and IC-PCE group consisted of 15 and 27 patients, respectively. Primary site was the oral cavity (n=25), oropharynx (n=3), hypopharynx (n=13) and larynx (n=1).Objective response rate (ORR) with IC-PCE was 55.6%; 24 patients (88.9%) subsequently received CRT.ORR after completion of CRT was significantly better in the IC-PCE group (95.8% in the IC-PCE group vs. 66.7% in the CRT group, p=0.024). Progression-free survival (PFS) of the total population on median followup of 2.4 years (range: 0.8-7.3) tended to be better in the IC-PCE group (2-year PFS: 55.6% in the IC-PCE group vs. 33.3% in the CRT group, log-rank p=0.176), especially in oral cancer (2-year PFS: 37.5% in the IC-PCE group vs. 0% in the CRT group, log-rank p=0.015).Therapeutic strategies including IC-PCE in patients with unresectable locoregional recurrent SCCHN after curative surgery may contribute to improved prognosis, especially in oral cancer.